Tinjauan terhadap Praktik Akad Ijarah dan Pembaruannya dalam Perkembangan Ekonomi Syariah di Lembaga Pegadaian Syariah Indonesia - Desiyanti, Nur Alfiyah; Wahyudi, Septi Andini Islamiyah; Huda, Bahrul (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
This research aims to make a significant contribution to understanding the practice of ijarah contracts in Islamic Pawnshop Institutions, potentially becoming a guide for practitioners, academics, and regulators in advancing the sharia economy in Indonesia. Focus of the research is on dynamics of the growing Islamic economy and the importance of ijarah as the main instrument in Islamic Pawnshop Institution. This research uses a Qualitative approach, this research method includes indirect data from the field and other parties. Secondary data sources are obtained from notes, journals, documentation articles related to ijarah contracts and their updates in the development of Islamic economics in Indonesia. The results concluded that the practice of ijarah in Indonesian Sharia Pawnshop Institution has complied with sharia principles, with important points such as transparency, free from usury, and strong sharia supervision. Technological updates, increased financial literacy, and product diversification are important elements in the renewal of ijarah practices. This research provides a comprehensive understanding in the context of Islamic economic development in Indonesia